The First Eocene Species of the Genus Micrambe (Coleoptera, Clavicornia, Cryptophagidae) - Lyubarsky, G.Yu.; Perkovsky, E.E. (Вестник зоологии, 2010)
Based on a fossil specimen from the Late Eocene Rovno amber (Ukraine), Micrambe sarnensis Lyubarsky et Perkovsky, sp. n., the first Eocene species of this genus is described. The new species is similar to the extant Micrambe abietis (Paykull) and M. ulicis (Stephens), differing by having the callosity with an acutangular caudolateral corner.